Assessment of the impact of the armed conflict in Ukraine on the development of the agricultural sector and price setting - Semenenko, Oleh; Minochkin, Anatolii; Vasylenko, Serhii; Klepikov, Valerii; Pravdyvets, Oleksandr; Правдивець, Олександр Миколайович (Polissia National University, 2021)
This paper analyses the impact of the armed conflict in Ukraine on the development of the agricultural sector and changes in average prices of agricultural products, and also identifies a possible relationship between changes in prices for agricultural products and financial expenditures for defence needs. The paper also investigates the possible relationship between changes in military spending, gross harvest of cereals and legumes, harvested and threshed area, their yield levels. The study considers how the presence and duration of armed conflict in the country affects: macroeconomic indicators, intensity of hostilities and their localisation in areas of economic activity, gross domestic product (GDP), government expenditures, export-import indicators; household expenditures and domestic investment, consumer and household expenditures. All this, indirectly, has an impact on fluctuations in average prices of products of different sectors of agriculture sold by enterprises. The study takes into account the importance of the agricultural sector of Ukraine, which is a significant part of the country GDP. The dependence of military spending on the size of GDP is the reason for analysing the relationship between the impact of the existing armed conflict on changes in the state of agriculture in Ukraine. One of the results of such actions was also the spending of more money on the purchase of agricultural products to support the defence needs of the state, etc. Therefore, to understand the magnitude of the impact of gross harvest factors, crop yields, and agricultural land volumes on the pricing of agricultural output using the method of statistical equation dependencies, the findings of the relevant analysis can be used as a basis for developing approaches, methods, and techniques to improve crop yields, or – initiate economic development of the country by increasing agricultural crop yields
Оцінювання впливу збройного конфлікту на території України на розвиток сільськогосподарської галузі та ціноутворення її продукції
Keywords: financial costs; macroeconomic indicators; gross domestic product; domestic investment; agricultural sector